IT AUDITORS' ENGAGEMENT IN TECHNOLOGY PROJECTS. Issue 4 (3rd April 2019) - McCabe, Krysten
Abstract: IT auditors are uniquely equipped to be strong contributors to technology projects, given their experience working with cross-functional teams and their ability to identify risks and suggest mitigating controls. As technology increasingly becomes a driver for enterprise projects, early involvement in those projects from IT auditors becomes critical to those projectsâ€ TM success and a key indicator of the value the IT audit function brings to the enterprise. Concerningly, recent ISACA research shows that only 35 percent of auditors are engaged in technology projects during the planning phase. This article provides guidance on how auditors can position themselves to make an earlier impact and why doing so is so crucial for the future of the IT audit profession.